2012
DOI: 10.1007/s00726-012-1420-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with monosodium glutamate is safe and improves growth performance in postweaning pigs

Abstract: Dietary intake of glutamate by postweaning pigs is markedly reduced due to low feed consumption. This study was conducted to determine the safety and efficacy of dietary supplementation with monosodium glutamate (MSG) in postweaning pigs. Piglets were weaned at 21 days of age to a corn and soybean meal-based diet supplemented with 0, 0.5, 1, 2, and 4 % MSG (n = 25/group). MSG was added to the basal diet at the expense of cornstarch. At 42 days of age (21 days after weaning), blood samples (10 mL) were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 49 publications
9
95
2
2
Order By: Relevance
“…Liquid milk replacer was prepared by diluting milk replacer powder (94.0% dry matter) 1:5 with warm water (dry matter 18.8%). This is similar to the dry matter content (18.6%) reported for sow's milk on d 7 -21 of lactation [15].…”
Section: Methodssupporting
confidence: 87%
“…Liquid milk replacer was prepared by diluting milk replacer powder (94.0% dry matter) 1:5 with warm water (dry matter 18.8%). This is similar to the dry matter content (18.6%) reported for sow's milk on d 7 -21 of lactation [15].…”
Section: Methodssupporting
confidence: 87%
“…Also, these results are paralleled with the results of Abdel-Rahim et al (1989) who found that, synthetic 43 colourants influenced as hypocholesterolemic and hypolipimic agents. The same observation was reported by Abdel-Rahim et al (1995), since they concluded that, total lipids and total cholesterol of blood were decreased by ingestion of synthetic colourants as food additives (Shi et al, 2010;Rezaei et al, 2013).…”
Section: Determination Of Fatty Acid Composition By (Gc-ms)supporting
confidence: 82%
“…Sows fed a basal gestational diet supplemented with mixture of 8 g L-arginine and 12 g L-glutamine had reduced withinlitter variation in birth weight either on the basis of total piglets or live-born piglets, and the proportion of runt piglets was decreased. It would be of interest to determine whether dietary supplementation with L-glutamate, which is the immediate precursor of L-glutamine (Rezaei et al, 2013b) and is another functional amino acid (Wu, 2010), can enhance fetal growth and reduce birth-weight variation among piglets.…”
Section: Glutaminementioning
confidence: 99%